Cardiopulmonary Bypass-Supported Coronary Artery Bypass Surgery: A Flexible and Effective Alternative to Off-Pump Surgery - Guven, Hakan; Cetintas, Demir (The Thoracic and Cardiovascular Surgeon, 2025)
This study aimed to compare the early postoperative outcomes of cardiopulmonary bypass-supported beating-heart coronary artery bypass grafting (CPB-BH CABG) and off-pump coronary artery bypass (OPCAB) surgery.A total of 589 patients who underwent beating-heart CABG between October 2021 and January 2025 were retrospectively analyzed. Patients were categorized into two groups based on CPB usage: CPB-BH CABG (n = 177) and OPCAB (n = 412). Primary outcomes included mortality and major complications, while secondary outcomes encompassed complete revascularization rates, number of distal anastomoses, hospital stay, and transfusion requirements.No significant differences were observed between the groups regarding preoperative characteristics. The CPB-BH group had longer operative times (268.7 vs. 223.6 minutes, p < 0.001) and prolonged hospital stays (7 vs. 5 days, p < 0.001). The rates of complete revascularization and the number of bypass grafts were slightly higher in the CPB-BH group, but did not reach statistical significance. The CPB-BH group required more blood transfusions (p < 0.001) and had a higher incidence of new-onset atrial fibrillation (33.9% vs. 24.0%, p = 0.016). No significant differences were found for other major complications.CPB-BH CABG is a viable alternative to OPCAB, offering comparable revascularization outcomes while allowing the flexibility of cardiopulmonary bypass support when needed. Surgeons should not hesitate to utilize CPB when necessary to optimize surgical outcomes. Future prospective, randomized controlled trials are warranted to assess the long-term outcomes of both surgical techniques and their effectiveness in specific patient subgroups.
Keywords: cardiac; cardiopulmonary bypass; CPB; coronary artery bypass graft surgery; CABG; ischemic heart disease; off-pump coronary artery bypass